2019
DOI: 10.1101/583674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of reduced host transcriptomic signatures for tuberculosis and digital PCR-based validation and quantification

Abstract: Recently, host whole blood gene expression signatures have been identified for diagnosis of tuberculosis (TB). Absolute quantification of the concentrations of signature transcripts in blood have not been reported, but would facilitate the development of diagnostic tests.To identify minimal transcript signatures, we applied a novel transcript selection procedure to microarray data from African adults comprising 536 patients with TB, other diseases (OD) and latent TB (LTBI), divided into training and test sets.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…Baseline characteristics of the study participants are shown in Supplementary Table 1 Of the 17 identified signatures ( Table 2), two were discovered from paediatric populations 28,29 . Four signature discovery datasets included HIV-infected and -uninfected participants 11,13,29,30 , one was discovered in an exclusively HIV-infected population for the purpose of active case finding 31 , while the remainder were discovered in HIV-negative populations. Four signatures were discovered with the intention of diagnosis of incipient TB [16][17][18] , with the remaining 13 discovered for diagnosis of active TB disease.…”
Section: Systematic Review Process and Summaries Of Included Datasetsmentioning
confidence: 99%
See 3 more Smart Citations
“…Baseline characteristics of the study participants are shown in Supplementary Table 1 Of the 17 identified signatures ( Table 2), two were discovered from paediatric populations 28,29 . Four signature discovery datasets included HIV-infected and -uninfected participants 11,13,29,30 , one was discovered in an exclusively HIV-infected population for the purpose of active case finding 31 , while the remainder were discovered in HIV-negative populations. Four signatures were discovered with the intention of diagnosis of incipient TB [16][17][18] , with the remaining 13 discovered for diagnosis of active TB disease.…”
Section: Systematic Review Process and Summaries Of Included Datasetsmentioning
confidence: 99%
“…The eight signatures that achieved equivalent performance were discovered with the primary intention of diagnosis of incipient TB [16][17][18] , or differentiating active TB from people who are healthy or with LTBI 12,13,30,37 .…”
Section: Eight Signatures Have Equivalent Diagnostic Accuracy For Incmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1 and Figure 1, the TB infection gene signature derived from different studies, represents associations with host innate immune responses such as B cell receptors, T cell receptors, Toll‐like receptors, and interferon (IFN) pathways 17–25 . Some other studies (Table 1) have also revealed a significant role of the NF‐κB pathway gene signature in TB pathogenesis 21,26 .…”
Section: Gene Signatures and Pathways Shared Between Tb And Ramentioning
confidence: 95%